2012
DOI: 10.1177/0042085911431472
|View full text |Cite
|
Sign up to set email alerts
|

Confronting the Marginalization of Culturally Responsive Pedagogy

Abstract: Globally, over the last two decades, attention to culturally responsive, multicultural approaches to teaching have largely been supplanted by standardized curricula and pedagogy that derive from neoliberal business models of school reform. In this essay, I discuss three factors that contribute to the marginalization of culturally responsive pedagogy: (a) a persistence of faulty and simplistic conceptions of what culturally responsive pedagogy is, (b) too little research connecting its use with student achievem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
363
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 514 publications
(378 citation statements)
references
References 58 publications
7
363
0
8
Order By: Relevance
“…This study supports Sleeter's (Sleeter, 2012), p. 578, claims that "small-scale case studies illustrate what is possible, but we also need research on the impact of scaled-up work in culturally responsive pedagogy, including research showing how teachers can learn to use it in their classrooms. " This study has several important implications.…”
Section: Resultssupporting
confidence: 56%
“…This study supports Sleeter's (Sleeter, 2012), p. 578, claims that "small-scale case studies illustrate what is possible, but we also need research on the impact of scaled-up work in culturally responsive pedagogy, including research showing how teachers can learn to use it in their classrooms. " This study has several important implications.…”
Section: Resultssupporting
confidence: 56%
“…Strong leadership, high expectations, strong motivation, hard work and effort are said to be what counts for successful school performances (Berhanu 2003;Höög and Johansson, 2009;Tomlin and Olusola 2012). Christine Sleeter (2012) suggests this emphasis on strong leadership has been a global tendency in the past two decades for solving problems of under-performance in school (Tomlin and Olusola 2012). Gewirtz (2002) contends it may exemplify some of the effects of a global neoliberal performativity turn in Western education systems.…”
Section: Introductionmentioning
confidence: 99%
“…Critical research studies claim that current research is of small scale, diluted from the original study, and are fragmented which therefore produces a disjointed and somewhat tedious understanding and stagnant practice (Sleeter, 2011(Sleeter, , 2012 This study seeks to answer the following research questions:…”
Section: Guiding Questionsmentioning
confidence: 99%
“…She concluded that all teachers showed growth in their understanding of culturally relevant teaching, but the group whose members immersed themselves understood much more intimately how their personal beliefs might affect the educational environment of their students of color (Bennett, 2012). Sleeter (2012) researched a professional development school connected to an urban teacher education program, seeking to observe how teachers were instructed in what it means to encompass a culturally relevant pedagogy. When Sleeter asked about the connection the school had built with the community it served, the educators said that the community was hard to reach, that they served more than one community, or that a community network had ceased to exist.…”
Section: Theory To Practice For Culturally Relevant Teachersmentioning
confidence: 99%
See 1 more Smart Citation